Numerical tests of an adaptive sectioned airfoil actuated by shape memory alloys - Maesta, Marcelo Francisco [UNESP]; Abreu, Gustavo Luiz C. M. de [UNESP]; Faria, Cassio Thome de; Lopes, Vicente [UNESP] (European Assoc Structural Dynamics, 2014)
The main objective of this work is to illustrate an application of angular active control in a sectioned airfoil using shape memory alloys. In the proposed model, one wants to establish the shape of the airfoil profile based on the determination of an angle between its two sections. This angle is obtained by the effect of the shape memory of the alloy by passing an electric current that modifies the temperature of the wire through the Joule effect, changing the shape of the alloy. This material is capable of converting thermal energy into mechanical energy and once permanently deformed, the material can return to its original shape by heating. Due to the presence of nonlinear effects, especially in the mathematical model of the alloy, this work proposes the application of a control system based on fuzzy logic. Through numerical tests, the performance of the fuzzy controller is compared with an on-off controller applied in a sectioned airfoil model.
Keywords: Adaptive sectioned airfoil; Shape memory alloys; Fuzzy control; On-off control